2006
DOI: 10.1002/esp.1352
|View full text |Cite
|
Sign up to set email alerts
|

The influence of grazing on vegetation, soil properties and stream discharge in a small Dartmoor catchment, southwest England, UK

Abstract: Intensive grazing has been responsible for environmental degradation of moorland landscapes over the last 50 years. Anecdotal evidence on Dartmoor, UK, for example, has suggested that it is particularly associated with a greater frequency of large floods, lower baseflow and a greater occurrence of erosion. A study was therefore conducted at Holne Moor, a small catchment on east Dartmoor, to investigate the impacts of grazing animals on hillslope hydrology and stream discharge. The vegetation in the study area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 15 publications
1
52
0
4
Order By: Relevance
“…Meyles et al, (2006) found that the land cover the highest stock densities (short grass = 1.24 sheep / hectare) (Figure 8.5a) had the lowest soil porosities (Figure 8.5b) and the highest soil bulk density (Figure 8.5c) for all soil depths.…”
Section: (Quartz)mentioning
confidence: 93%
See 3 more Smart Citations
“…Meyles et al, (2006) found that the land cover the highest stock densities (short grass = 1.24 sheep / hectare) (Figure 8.5a) had the lowest soil porosities (Figure 8.5b) and the highest soil bulk density (Figure 8.5c) for all soil depths.…”
Section: (Quartz)mentioning
confidence: 93%
“…This highlights the importance of predicting soil moisture dynamics as a diagnostic tool for flood generation. Meyles et al, (2006) found that changes to the physical characteristics of the soil (decreased organic content, increased bulk density, decreased porosity) caused the wetness threshold between dry and wet states was lower in heavily grazed area, as field capacity was reached more readily.…”
Section: Figure 910 Proportion Of Rainfall That Is Partitioned Into mentioning
confidence: 99%
See 2 more Smart Citations
“…Runoff is greater from heavily grazed land (Evans, 1990b(Evans, , 1998, especially from those areas particularly favoured by sheep (Meyles et al, 2001), because the vegetation cover is very low or thin and soils are more compact. Furthermore, tracking and channeling of water downslope speed runoff into channels.…”
Section: Grazing Of Uncultivated Landmentioning
confidence: 99%